The Legal Regulation of the Right for Installing and using surveillance cameras- Analytical and Comparative Study - Hussain, Esmail Namiq; Al-Dalawi, Bamo Parwez Khan (Journal of Legal and Political Studies, 2020)
This research follows a comparative and analytical approach to study the issue of the right to install and use surveillance cameras in both Iraqi law, Kuwaiti and Qatari law. It is observed that Iraq has not regulated this issue with a special law but rather by a decision issued by the Council of Ministers. Despite the fact that Kuwait and Qatar have a special law that regulates most of Its aspects and provisions, but it is noted that gaps and deficiencies exist in them. Through this research, it is found that organizing this topic is based mainly balancing and comparing between the right to privacy and the right to live in safety or the Right to Protection. As a result of this comparison, the installation of cameras and security monitoring devices has become obligatory in places, prohibited in other places and permissible in other (third) places. Based on a careful observation and evaluation of that balancing and comparison, and the believe that there is a need for a law in this arena in the Kurdistan-Iraq region; this research has proposed a draft safety law for the use of security cameras and surveillance devices.
Keywords: right to install; surveillance cameras; Kuwaiti and Qatari law; Council of Ministers; Right to Protection